Assim na terra como no ce??u. - Bastos, Ma??rio Jorge da Motta, 1963- author. Link
1 online resource (256 pages)
Keywords: Addressing fundamental questions of the conversion of the West to Christianity between the 4th and 8th centuries, this book explores how and why new religions spread in societies that were previously foreign to them, and examines what happens to the old gods and traditional beliefs in this process. The slow penetration and spread of Christianity in the rural areas of the post-Roman West, with the contradictions that characterized it, can only be fully understood through its integration into the more global process that was underway at this time, namely the development of new relations of power and domination. The book takes a theoretical approach to the transition from Antiquity to the Middle Ages in the Iberian Peninsula and investigates the themes of the process of the dissemination of Christianity and 'pagan' resilience, and the relationship of the establishment of the Church with the development of new power relations and the domination of the aristocracy over the peasantry.